Active Database System Approach and Rule Based in the Development of Academic Information System - Miftakul Amin, M; Maseleno, Andino; K, Shankar; Perumal, Eswaran; M Vidhyavathi, R; SK, Lakshmanaprabu (International Journal of Engineering and Technology, 2018)
Active database system is a database system which isÂ capable of generating a certain action automatically if it detects an event that meets certain conditions. The existence of Event Condition Action (ECA) rules and functional components such as triggers, stored procedures, and stored functions that are owned by active database system make the database system has the ability to automatically monitor input and output data. Separation of ECA rules components in the database with the application program will also facilitate the development of information systems. This research applies active database system in academic information system, so that academic business rules can be planted in database software and be able to produce the right solution automatically. The addition of active database system components to the database software makes procedures such as subject distribution, study plans, academic leave, values, thesis defense and other processes can be monitored by the system automatically. This can be done because between applications and databases use the model driven approach parameters to communicate with each other. The results of this research prove that a database is not only hasÂ function as a container of data, but can control the information system actively, this is caused by the logic of programs that are generally planted in the application layer that can be moved and planted in the database software.